Accelerating Financial Inclusion Through Mobile Phone Technology: Opportunities, Challenges And Policy Options For India. - Sumanjeet (2011)
Technology is the key for financial inclusion because that is the only way to reduce the cost significantly and reach the masses. But all technologies are not suitable for financial inclusion owing to affordabiltiy, accessibility, security and privacy. In the last decade, mobile phone technology has emerged as the most potential and well suited channel for financial inclusion. Use of mobile phones for inclusive finance is very popular in countries where most of the population is unbanked or underbanked. The Indian government has also realized that the mobile phone can be an important mode for propagation of financial inclusion in the country. As a result, the Indian government has already taken many initiatives to promote mobile banking as a tool to expand the credit and financial services to the excluded populations. But, the mobile phone, although a critical tool of financial inclusion, does not guarantee adoption, it only indicates potential. There are many challenges in adoption and successful implementation of mobile technology especially in rural areas. In the present paper an attempt has been made to explore the potential of mobile phone technology in accelerating financial inclusion in India. The paper also highlights pitfalls of the mobile technology for financial inclusion. Further, the paper makes an attempt to discuss the policy options, which needs to be done to ensure equitable access to financial services for all who want it..